2009
DOI: 10.1111/j.1600-0706.2008.17168.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐flowering neighbors influence the diversity and identity of pollinator groups visiting plant species

Abstract: The generalization–specialization continuum exhibited in pollination interactions currently receives much attention. It is well‐known that the pollinator assemblage of particular species varies temporally and spatially, and therefore the ecological generalization on pollinators may be a contextual attribute. However, the factors causing such variation and its ecological and evolutionary consequences are still poorly understood. This variation can be caused by spatial or temporal variation in the pollinator com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 71 publications
6
112
0
2
Order By: Relevance
“…For example, shape preferences of butterflies, honeybees and beeflies varied across years, such that in 2007 open flowers did not show a higher level of ecological generalization than closed flowers. This result may be due to variation in the structure of the community (McCall and Primack 1992; Hingston and McQuillan 2000;Ollerton et al 2007;Lázaro et al 2008Lázaro et al , 2009). …”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, shape preferences of butterflies, honeybees and beeflies varied across years, such that in 2007 open flowers did not show a higher level of ecological generalization than closed flowers. This result may be due to variation in the structure of the community (McCall and Primack 1992; Hingston and McQuillan 2000;Ollerton et al 2007;Lázaro et al 2008Lázaro et al , 2009). …”
Section: Discussionmentioning
confidence: 80%
“…2). This non-significant result in 1 year could be because the realized pollinator generalization level was influenced not only by floral traits but also by community structure (both composition and abundance of plants and pollinators) (McCall and Primack 1992;Hingston and McQuillan 2000;Ollerton et al 2007;Lázaro et al 2008Lázaro et al , 2009). Lázaro et al (2008) demonstrated that closed flowers were more generalized than open flowers in one of three Scandinavian plant communities because of the variation in composition of the pollinator assemblage.…”
Section: Pollination Generalization Levelmentioning
confidence: 89%
See 1 more Smart Citation
“…Sites were analyzed separately and responses compared using t tests or z tests ( Feinsinger 1987;Ghazoul 2006;Rathcke 1983). Plant density and diversity affect both the composition and abundance of pollinators on plants (Conner and Neumeier 1995;Hegland and Totland 2005;Lazaro et al 2009;Moeller 2005), consistent with the idea that L. maackii affected the composition and abundance of pollinators on H. macrophyllum. Data from our pollinator observations suggest that L. maackii attracted to the plots a variety of pollinator species that also visited H. macrophyllum; we found more pollinator taxa on H. macrophyllum in plots in which L. maackii was present.…”
Section: Reproductive Outputmentioning
confidence: 98%
“…De qualquer maneira, a similaridade na composição destas comunidades é baixa: cinquenta e sete das espécies vegetais floridas foram de ocorrência exclusiva de alguma das áreas, sendo RD3 e RA3 as áreas com maior número de ocorrências exclusivas (19 e 14 respectivamente), seguidas de RA1 (11), (Lázaro et al 2009). …”
Section: Discussionunclassified